Access to and interventions to improve maternity care services for immigrant women: a narrative synthesis systematic review - Gina MA Higginbottom; Catrin Evans; Myfanwy Morgan; Kuldip K Bharj; Jeanette Eldridge; Basharat Hussain; Karen Salt (National Institute for Health Research, 2020)
Background: In 2016, over one-quarter of births in the UK (28.2%) were to foreign-born women. Maternal and perinatal mortality are disproportionately higher among some immigrants depending on country of origin, indicating the presence of deficits in their care pathways and birth outcomes. Objectives: Our objective was to undertake a systematic review and narrative synthesis of empirical research that focused on access and interventions to improve maternity care for immigrant women, including qualitative, quantitative and mixed-methods studies. Review methods: An information scientist designed the literature database search strategies (limited to retrieve literature published from 1990 to 2018). All retrieved citations (45,954) were independently screened by two or more team members using a screening tool. We searched grey literature reported in related databases and websites. We contacted stakeholders with subject expertise. In this review we define an immigrant as a person who relocates to the destination country for a minimum of 1 year, with the goal of permanent residence. Results: We identified 40 studies for inclusion. Immigrant women tended to book and access antenatal care later than the recommended first 10 weeks of pregnancy. Primary factors included limited English-language skills, lack of awareness of availability of the services, lack of understanding of the purpose of antenatal appointments, immigration status and income barriers. Immigrant women had mixed perceptions regarding how health-care professionals (HCPs) had delivered maternity care services. Those with positive perceptions felt that HCPs were caring, confidential and openly communicative. Those with negative views perceived HCPs as rude, discriminatory or insensitive to their cultural and social needs; these women therefore avoided accessing maternity care. We found very few interventions that had focused on improving maternity care for these women and the effectiveness of these interventions has not been rigorously evaluated. Limitations: Our review findings are limited by the available research evidence related to our review questions. There may be many aspects of immigrant women's experiences that we have not addressed. For example, few studies exist for perinatal mental health in immigrant women from Eastern European countries (in the review period). Many studies included both immigrant and non-immigrant women. Conclusions: Available evidence suggests that the experiences of immigrant women in accessing and using maternity care services in the UK are mixed; however, women largely had poor experiences. Contributing factors included a lack of language support, cultural insensitivity, discrimination and poor relationships between immigrant women and HCPs. Furthermore, a lack of knowledge of legal entitlements and guidelines on the provision of welfare support and maternity care to immigrants compounds this. Future work: Studies are required on the development of interventions and rigorous scientific evaluation of these interventions. Development and evaluation of online antenatal education resources in multiple languages. Development and appraisal of education packages for HCPs focused on the provision of culturally safe practice for the UK's diverse population. The NHS in the UK has a hugely diverse workforce with a vast untapped linguistic resource; strategies could be developed to harness this resource. Study registration: This study is registered as PROSPERO CRD42015023605. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 14. See the NIHR Journals Library website for further project information.